(untitled) (Economic and Political Thought, 2019)
The article shows the attempts to overthrow the USSR’s hegemony over Poland of the Solidarity camp which on 4 June 1989 won the first free post-war parliamentary elections in Poland. The author presents views and intentions of communists removed from power as a result of the elections from the camp of which the then Polish president, Wojciech Jaruzelski, came from. The amended constitution of the People’s Republic of Poland equipped the president with enormous competences. The article reports the history of the president-communist in times of nascent democracy in Poland and his relations with the USSR, who, however, did not take any steps to hinder Poland’s accession to the European Union and NATO. The study argues with the thesis that the government pursued the policy of Finlandisation. The author reached for the files from the Presidential Archives and the PPR Historical Records Archive Foundation, not used so far in analyses of international relations.